(untitled) (Bioscience Journal, 2022)
The present work aimed to evaluate the influence of Stylosanthes spp. (Campo Grande© styles) and Brachiaria brizantha cv. Marandu in the vertical migration of Haemonchus spp. infective larvae, in the region of Uberlândia, Minas Gerais. Seeds of Stylosanthes spp. and Brachiaria brizantha cv. Marandu were planted in 50 pots of five liters (20 cm diameter) evenly disposed in an area of the Capim Branco Experimental Farm, Federal University of Uberlândia. When both species reached the minimum height of 20 cm, the pots were experimentally contaminated with sheep feces coprocultures. Samplings were performed, with complete removal of the vegetal material contained in the pots, on days one, three, six, 10 and 14 after contamination. Nematoids were recovered from the plant samples by thermo and hydrotropism, counted under an optical microscope and identified. For statistical analysis, the data were analyzed in a completely randomized design (DIC) in a 2X5 factorial scheme (two fodder species X 5 collection dates). No effect of the forage species was observed on the number of L3 of Haemonchus sp. recovered in the feces (p = 0.7790), upper stratum (p = 0.1755) or lower stratum (p = 0.7883) of the forage, however, there was a significant decrease in the number of L3 found with the passing of the days. When comparing the mean L3 recovered in the upper (0.06±0.31 L3) and lower (2.94±0.39) strata, a higher number of larvae was observed in the lower stratum (p < 0.0001). Therefore, in both forage species studied, the upper stratum of the plants, preferably pastured by the animals, remained with less contamination of infective larvae and the contamination tended to decrease over the days.